Leave Duration After Childbirth: Impacts on Maternal Mental Health, Parenting, and Couple Relationships in Australian Two-Parent Families. (October 2013) - Whitehouse, Gillian; Romaniuk, Helena; Lucas, Nina; Nicholson, Jan
In this article, we use longitudinal data on Australian two-parent families to assess the impact of mothers' leave duration after childbirth on their subsequent mental health, quality of parenting, and couple relationships. We found that 2 to 3 years after the birth, psychological distress was significantly less likely among mothers who took >13 weeks paid leave or >26 to 52 weeks leave in total. However, those who took >26 weeks in total were more likely to register as "distant" in their parenting relationship. The analysis also highlighted the importance of leave supports at the workplace: Mothers who experienced workplace problems during their pregnancy were more likely to report feeling rushed and to rate their couple relationship as unhappy or argumentative 2 to 3 years later. Overall, our study underlined the complexity of leave impact but affirmed the importance of leave duration for maternal mental health and leave takers' workplace supports for maternal and family outcomes.